Recreational Harvesting of the Florida Bay Scallop: Hernando County - Brittany Hall-Scharf (EDIS)
A full-color map identifying access routes to the boat ramps and marinas in Hernando County, plus the latest information on scallops and scalloping, the recommended equipment you will want to bring, and a few tasty recipes for preparing Florida’s best summertime catch.